2018
DOI: 10.1111/imm.12925
|View full text |Cite
|
Sign up to set email alerts
|

Innate‐like CD8+ T‐cells and NK cells: converging functions and phenotypes

Abstract: SummaryNew data in the worlds of both innate‐like CD8+ T‐cells and natural killer (NK) cells have, in parallel, clarified some of the phenotypes of these cells and also their associated functions. While these cells are typically viewed entirely separately, the emerging innate functions of T‐cells and, similarly, the adaptive functions of NK cells suggest that many behaviours can be considered in parallel. In this review we compare the innate functions of CD8+ T‐cells (especially mucosal‐associated invariant T‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 144 publications
(283 reference statements)
4
39
0
Order By: Relevance
“…One possibility is that the CD8 T cells in the lesions are inducing non‐specific killing of healthy tissue. Previous studies have shown that senescent CD8 + T cells acquire the expression of functional NK receptors . Furthermore, inflammation and also the development of senescence induces the expression of NK ligands in tissue cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that the CD8 T cells in the lesions are inducing non‐specific killing of healthy tissue. Previous studies have shown that senescent CD8 + T cells acquire the expression of functional NK receptors . Furthermore, inflammation and also the development of senescence induces the expression of NK ligands in tissue cells .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that senescent CD8 + T cells acquire the expression of functional NK receptors. 30,31 Furthermore, inflammation and also the development of senescence induces the expression of NK ligands in tissue cells. 31 Therefore, skin-homing CD8 + T cells in CL may mediate non-specific pathology by killing NKR-ligand-expressing cells such as fibroblasts and keratinocytes in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…If understanding of NK cell function is making them appear ever more adaptive in behaviour, some aspects of CD8 T-cell function are coming to be appreciated as nearer to that of innate immune populations. 9 Willberg and colleagues have pointed out the similarities between the cytokine-driven programmes of CD161 + CD8 mucosa-associated invariant T (MAIT) cells and CD56 bright NK cells. They make a persuasive case that sometimes, rather than immunology seeking to split cells into smaller and smaller subsets, it may sometimes be informative to be 'lumpers' rather than 'splitters'!…”
Section: Discussionmentioning
confidence: 99%
“…If understanding of NK cell function is making them appear ever more adaptive in behaviour, some aspects of CD8 T‐cell function are coming to be appreciated as nearer to that of innate immune populations . Willberg and colleagues have pointed out the similarities between the cytokine‐driven programmes of CD161 + CD8 mucosa‐associated invariant T (MAIT) cells and CD56 bright NK cells.…”
mentioning
confidence: 99%
“…While altered circulating B-and NK cell frequencies may not be of direct relevance in the pathogenesis of psoriasis, 12,13,71 both lymphocyte subsets contribute to the immune response against infections, including those of a viral nature. [72][73][74] Drugs containing FAEs are used to treat psoriasis (Fumaderm â , FAEs; Skilarence â , DMF; and Psorinovo â , DMF, compounded pharmacy) and MS (Tecfidera â , DMF). All licensed FAE drugs contain DMF as the main active ingredient, which acts as an orally administered prodrug of MMF in vivo.…”
Section: Biological Effects Of Faes On Peripheral Blood Lymphocytesmentioning
confidence: 99%